Mispricing of Sovereign Risk and Multiple Equilibria in the Eurozone - Paul De Grauwe; Yuemei Ji (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
We find evidence that a significant part of the surge in the spreads of the PIGS countries in the Eurozone during 2010-11 was disconnected from underlying increases in the debt to Gdp ratios, and was the result of negative market sentiments that became very strong since the end of 2010. We also find evidence that after years of neglecting high government debt, investors became increasingly worried about this in the Eurozone, and reacted by raising the spreads. No such worries developed in stand-alone countries despite the fact that debt to Gdp ratios were equally high and increasing in these countries. We interpreted this evidence as validating the hypothesis firmulated in De Grauwe(2011) according to which government bond markets in a monetary union are more fragile and more susceptible to self-fulfilling liquidity crises than in stand-alone countries. We argue that the systematic mispricing of sovereign risk in the Eurozone intensifies macroeconomic instability, leading to bubbles in good years and excessive austerity in bad years.
Keywords: 330; Länderrisiko; Öffentliche Anleihe; Wirtschaftliche Instabilität; Europäische Wirtschafts- und Währungsunion; Griechenland; Irland; Italien; Portugal; Spanien